New Media Usage and Its Perceived Effects on Classroom Communication and Learning Behavior - Vera, Patricia Ann E. (International Journal on Open and Distance e-Learning, 2016)
The study delves on how new media tools have impacted classroom communication and learning behavior. Conducted at the Assumption College among college students and professors, the study showed that there is no relationship between new media tools usage with learning behaviors of self-efficacy and motivation. However, it was found that there’s a strong relation between technological competence and motivation and self- efficacy. Further, it was also shown that the ubiquity of technology has not been fully utilized in classroom communication.